Development of a Smart Coffee Model Based on the Internet of Things (IoT) in West Java Province - Nastiti, Tashia Indah; Sintha Wahjusaputri; Bunyamin, Bunyamin; Johan, Johan (Universitas Budi Darma, 2025)
Coffee cultivation in fertile regions such as Ciniru District, Kuningan Regency, is still predominantly carried out manually, lacking adequate technological support. However, coffee plants require intensive monitoring of environmental conditions to ensure optimal productivity and quality. The absence of technology adoption in farming practices results in inefficiencies and makes the cultivation process vulnerable to pests and climate-related disruptions. This study aims to develop a smart monitoring system for coffee plantations in Gunung Manik Village, utilizing an Internet of Things (IoT)-based Smart Coffee model. The system is designed to assist coffee farmers in Kuningan in improving yields and providing guidance for crop management through real-time monitoring of soil moisture, environmental temperature, and pest activity. An experimental method was employed in this research, where data is transmitted via radio frequency to a gateway and subsequently forwarded to middleware for further processing. The processed data is then visualized through a dashboard and a mobile-based application. Currently, the system is focused on a single variety of coffee plants. The results demonstrate that the system provides accurate data for irrigation and fertilization scheduling, as well as notifications regarding plant conditions, growth stages, and cultivation status. In conclusion, the coffee plant monitoring system offers a practical digital solution for farmers and is expected to enhance agricultural productivity through the integration of information technology.